Robust braid reinforced hollow fiber membranes for organic solvent nanofiltration (OSN) - Zhen-Yuan Wang; Ru Feng; Wei-Jian Wang; Yu-Xuan Sun; Sheng-Nan Tao; Yi-Meng Wang; Ya-Feng Chen; Zheng-Jun Fu; Xue-Li Cao; Shi-Peng Sun; Weihong Xing (Advanced Membranes, 2021)
The hollow fiber organic solvent nanofiltration (OSN) membranes have drawn increasing interest for the refining of high value-added products such as nutraceuticals, pharmaceuticals and fine chemicals. The hollow fiber OSN membranes with defined pore size, reliable stability and durability in various harsh solvents are in urgent demand. Herein, for the first time, braid reinforced hollow fiber (BRHF) OSN membranes with defined pore size, robust mechanical strength, and excellent solvent stability were fabricated and used for the recovery of pharmaceuticals. The BRHF nanofiltration membranes can endure an operation pressure over 3 times larger than that of the cross-linked polyimide hollow fiber OSN membranes in aprotic solvents with a DMF flux of 37.9 LMH and a methanol flux of 70.3 LMH at 15 ​bar. The membranes show over 98.8% rejection to the Tetracycline, Chlortetracycline hydrochloride and Vitamin B12. After immersion in DMF for 360 ​h, the membranes maintain over 98% rejection to Chlortetracycline hydrochloride. Moreover, the BRHFs eliminate the risk of module leakage caused by breakage of hollow fibers and surmount the swelling tendency of polymeric OSN membranes in harsh solvents which enables the scaling-up of high-performance hollow fiber OSN membrane modules. The BRHF OSN membranes with robust stability and durability exhibit very promising application prospects in the pharmaceutical and fine chemical industry.